Volatility and Market Integration of Spot-Forward Corn Price in Indonesia - Octaviana Helbawanti; Masyhuri - (MediaTrend, 2019)
This study aims to determine the volatility and market integration between the price of corn in the Indonesian spot market and futures market in the international market. The data used in this research is secondary data consisting of Indonesian corn spot price and corn forward price referring commodity exchange, Chicago. Data in the form of monthly time series in 2007 until 2016. ARCH / GARCH method is used to measure the volatility at spot and forward price, whereas the market integration of spot and forward corn is used Johansen Cointegration and Engel-Granger Causality method. The results show that spot and forward prices of corn occur high volatility. The best ARCH/GARCH model for spot price is GARCH (2,0) with the volatility value of 0,91 and for forward price is GARCH (2,0) with the volatility value of 1.12. It means that volatility of spot and forward influenced by the increase and fluctuations of spot and forward price two previous periods. Between the spot and forward market, there is market integration and a one-way causal relationship. The market integration indicates there is long-run relationship, while one way indicates the spot price effect on the forward price, not vice versa.